Analysis of the interactive activities to improve oral fluency in the sixth grader students from República de Francia Elementary School - Cáceres, Katherine; Pitti, Joshua (David, Panamá : UDELAS, 2015)
Oral communication is a complex process of a language, Interactive activities will provide our students good opportunities to increase therir knowledge in a second language especially in oral fluency to achieve a good level of communication with other people.
TABLE OF CONTENTS CHART INDEX GRAPHIC INDEX INTRODUCTION I. CHAPTER I: ANTECEDENTS AND STATEMENT OF THE PROBLEM 1.1. Antecedents 1.2. Statement of the problem 1.3. General objective 1.3.1. General objective 1.3.2. Specific objectives 1.4. Justification 2. CHAPTER II: THEORICAL FRAMEWORK 2.1. Interactive activities 2.1.1. Interactive activities for promoting oral communication in class 2.1.2. Importance of the interactive activities in oral communication skills 2.1.3. Characteristics of the interactive activities 2.2. Types of interacative activities 2.2.1. Based on role plays 2.2.2. Based on group work 2.2.3. Based on cooperative learning 2.2.4. Based on technology 2.3. Advantages 2.3.1. Opportunities for students participation 2.3.2. Improvement of oral expression 2.3.3. Developing oral fluency 2.3.4. Promote english learning 2.4. Role of the teacher in the interactive activities 2.4.1. Application of interactive activities 2.4.2. Motivate students 2.4.3. Organize interactive activities 2.4.4. Classroommanagement 2.5. Role of students in the interactive activities 2.5.1. Active participation 2.5.2. Following instructions 2.5.3. Classroom environment 2.6. Examples of interactive activities 2.6.1. Class discussion 2.6.2. Class survey 2.6.3. Finish the story 2.6.4. What do you do if 2.6.5. Cultural exchange 2.6.6. Simulations 2.6.7. Brainstorming 3. CHAPTER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.2. Information sources 3.3. Subjects 3.4. Hypothesis 3.5. Variable system 3.6. Stratey or methodological design for data collection and manipulation 4. CHAPTER IV: ANALYSIS AND RESULT CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEXES
Incluye Chart index
Incluye Graphic index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; ORAL COMMUNICATION -- TESIS DE LICENCIATURA; DOCENCIA EN INGLÉS; REPUBLICA DE FRANCIA ELEMENTARY SCHOOL